2021
DOI: 10.1007/s13311-021-01067-w
|View full text |Cite|
|
Sign up to set email alerts
|

Nutritional Ketosis in Parkinson's Disease — a Review of Remaining Questions and Insights

Abstract: Nutritional ketosis has promise for treating Parkinson’s disease. Three previous studies explored the use of a ketogenic diet in cohorts with Parkinson’s disease, and, while not conclusive, the data suggest non-motor symptom benefit. Before the ketogenic diet can be considered as a therapeutic option, it is important to establish with greater certainty that there is a reliable symptomatic benefit: which symptoms or groups of symptoms are impacted (if non-motor symptoms, which ones, and by which mechanism), wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 97 publications
0
14
0
Order By: Relevance
“…ough the exact pathology of PD remains elusive, the oxygen free radicals, trophic factors loss, altered calcium homeostasis, and neuroinflammation have been supposed to be involved [6,[43][44][45]. However, these pathological processes associated with PD might be alleviated by the multiple neuroprotective mechanism of ketosis induced by KD [46][47][48][49]. e anti-inflammatory properties of KD also have been verified in other neurological disorders associated to neuroinflammation, including multiple sclerosis, pain, epilepsy, AD, and spinal cord injury [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…ough the exact pathology of PD remains elusive, the oxygen free radicals, trophic factors loss, altered calcium homeostasis, and neuroinflammation have been supposed to be involved [6,[43][44][45]. However, these pathological processes associated with PD might be alleviated by the multiple neuroprotective mechanism of ketosis induced by KD [46][47][48][49]. e anti-inflammatory properties of KD also have been verified in other neurological disorders associated to neuroinflammation, including multiple sclerosis, pain, epilepsy, AD, and spinal cord injury [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the effects of a ketogenic diet by itself, without exercise therapy, on PD subject symptoms have recently been reviewed [ 132 ]. Unlike the results from mouse models of PD where the ketogenic diet has shown moderate protective effects, the clinical results from PD subjects showed that the diet did not affect motor symptoms and only showed slight improvements in the non-motor symptoms [ 133 ].…”
Section: Interventional Strategies To Correct Dysfunctional Mqc and D...mentioning
confidence: 99%
“…At a sufficient degree of ketosis, the direct signal effect of the ketone body can induce the gene expression of antioxidant enzymes, reduce apoptosis through a metabolic state similar to fasting, and theoretically increase neurotransmitters. A ketogenic diet with a high percentage of fat, a low percentage of carbohydrates, protein, and other nutrients that cause nutritional ketosis in PD patients has indeed been found to ameliorate the condition to some extent ( Phillips et al, 2018 ; Choi et al, 2021 ).…”
Section: Treatmentmentioning
confidence: 99%